Molecular Dynamics of Thermoalkalophilic Lipases Unfolding At High Temperatures - Karjiban, Roghayeh Abedi (2008)
The structure, dynamics and flexibility of thermoalkalophilic lipases of Bacillus stearothermophilus L1 (L1 lipase) and Geobacillus zalihae strain T1 (T1 lipase) were successfully explored through molecular dynamics simulation (MD) technique. MD simulations at extremely high temperature in explicit solvent were carried out to understand how a thermoalkalophilic lipase starts to unfold at high temperature. The simulations were performed at 400 K and 500 K in addition to a control simulation at 300 K for a total of 12.0 ns. The high stability of both global three-dimensional (3D) structures at control simulation was confirmed by a good correlation between crystallographic experimental and simulated B-factors. The systematic flexibility and dynamics of both systems were analyzed using the timeaveraged root mean square fluctuations (RMSf) and the root mean square deviations (Cα- RMSd). Both systems showed a very similar flexibility and dynamics at 300 K and 400 K while at 500 K, L1 lipase showed more flexibility than T1 lipase. The average RMSf and the Cα-RMSd results for both systems were in a good agreement, indicating that thermostability was correlated with higher flexibility rather than increased rigidity in our model systems. Both L1 lipase and T1 lipase structures maintained their global 3D structures and did not undergo any significant unfolding process at 400 K, while both structures lost their structures partially at 500 K. The results clearly illustrated that the N-terminal moiety of both model systems showed high flexibility and dynamics during thermal unfolding simulations which preceded and followed by clear structural changes in two specific regions; the small extra domain (consisting of helices α3 and α5, strands β1 and β2, and connecting loops) and the main catalytic domain or core domain (consisting of helices α6- α9 and connecting loops which are located above the active site of the enzyme). The two domains of both systems interact with each other through a Zn2+-binding coordination with Asp61 and Asp238 from the core domain and His81 and His87 from the small domain via tight interactions. Interestingly, the His81 and His87 were among the highly fluctuated residues at high temperatures while Asp61 and Asp238 did not show any significant fluctuations. The results indicated that these tight interactions became very weak at high temperatures which presumably contributed to the thermostability of both enzymes. The results also suggested that the initial steps in the unfolding of a thermoalkalophilic lipase may involve early loss of structure in the small extra domains of these enzymes followed by core opening. Therefore, the N-terminal moiety and the small domain of both enzymes are critical regions to thermostability and they can be a potential target for stability enhancement.